Erratum: Signal denoising optimization based on a Hilbert-Huang transform-triple adaptable wavelet packet transform algorithm. (25th January 2019) - Liu, Fei; Zhang, Yongjun; Yildirim, Tanju; Zhang, Jiawei
Abstract: Original article: EPL, 124 (2018) 54002 .